2017
DOI: 10.1093/annonc/mdx352
|View full text |Cite|
|
Sign up to set email alerts
|

Global patterns of care in advanced stage mycosis fungoides/Sezary syndrome: a multicenter retrospective follow-up study from the Cutaneous Lymphoma International Consortium

Abstract: This large multicenter retrospective study shows that there exist a large treatment heterogeneity in advanced MF/SS and differences between USA and non-USA centers but these were not related to survival, while our data reveal that chemotherapy as first treatment is associated with a higher risk of death and/or change of therapy and thus other therapeutic options should be preferable as first treatment approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 30 publications
5
92
2
5
Order By: Relevance
“…This shared a similarity with the global patterns of MF put forward by a multicentre retrospective followup study. 1 One study reported that the incidence of CTCL and MF is higher among African American than white individuals in the U.S.A., with earlier onset and more advanced disease, and median age at diagnosis of MF was 47 years, older than in our findings. 2 We also observed from one study that perhaps Asian patients with MF were younger than white, black and mixed-race patients.…”
contrasting
confidence: 68%
“…This shared a similarity with the global patterns of MF put forward by a multicentre retrospective followup study. 1 One study reported that the incidence of CTCL and MF is higher among African American than white individuals in the U.S.A., with earlier onset and more advanced disease, and median age at diagnosis of MF was 47 years, older than in our findings. 2 We also observed from one study that perhaps Asian patients with MF were younger than white, black and mixed-race patients.…”
contrasting
confidence: 68%
“…CTCL is an uncommon but devastating malignancy in advanced stages, with a median survival of <5 years. 29 Geographic clustering has been identified in several regions nationally and internationally, particularly in urban and industrial regions. [10][11][12][13][14] However, the environmental risk factors for CTCL have not been previously evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Quaglino et al . published a retrospective analysis of 853 patients with advanced MF/SS from 21 centres . This large, multicentre retrospective study showed a substantial heterogeneity of treatment approaches in advanced MF/SS between U.S. and non‐U.S.…”
Section: Treatment Of Mycosis Fungoides/sézary Syndromementioning
confidence: 99%